Anharmonic phonon scattering and strain-tunable thermal conductivity in AlGaAs 2 DLHC monolayer - Rivera, Victor José Ramirez; Gonzalo, Fredy Mamani; Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Laura, Gohnny Acero [UNESP]; Simoes, A.Z. [UNESP]; Sambrano, Julio R. [UNESP]; Piotrowski, Maurício Jeomar; Flores, Efracio Mamani (Elsevier, 2025)
The emergence of double-layer honeycomb (DLHC) monolayers has broadened the design space of two-dimensional (2D) materials by enabling the stabilization of low-energy configurations of traditional III–V semiconductors. Among them, DLHC-AlGaAs 2 has recently attracted attention due to its predicted dynamic and thermodynamic stability, although its physical behavior under strain remains unexplored. In this study, a comprehensive first-principles investigation of the structural, electronic, and phonon transport properties of DLHC-AlGaAs 2 under biaxial strain was carried out. The results obtained reveal that strain profoundly influences phonon dynamics: tensile strain increases lattice anharmonicity, reflected in higher Grüneisen parameters and shorter phonon lifetimes, which in turn enhance phonon–phonon scattering. This leads to a notable reduction in lattice thermal conductivity ( κ l ) from 3.72 to 3.05 Wm−1K−1 as the strain is varied from − 2 % to + 2 % . The thermal transport is primarily governed by acoustic phonons, whose group velocities and mean free paths exhibit strong strain dependence. Given its pronounced sensitivity to strain and the resulting tunability of its thermal transport behavior, DLHC-AlGaAs 2 emerges as a strong candidate for integration into 2D thermoelectric and nanoscale electronic systems where efficient heat management is essential.